Rehabilitation using neurodevelopmental and sensory integration therapy approaches in an 8-month-old infant with self-gratification behavior: A case report (Indian Journal of Case Reports, 2024)
Self-gratification behavior is a normal behavior in infants or children and is usually misdiagnosed with dystonic development delays, repeated movement disorders, or even epilepsy. This case report aims to share our clinical experience in managing a child with self-gratification disorder through physical therapy techniques. An 8-month-old female infant presents with concerns related to poor social interaction, reduced play, irritable behavior, frequent crossing, and stiffness in the legs which she started showing at 3 months of age. She was earlier diagnosed with dystonic developmental delay and referred for a thorough development and sensory assessment. Rehabilitation with sensory integration and neurodevelopmental techniques was delivered to the child. Ages and Stages Questionnaire, Denver’s score, and Sensory profile were assessed at 8–9 months, 9–10 months, and 10–11 months to monitor prognosis. There was a significant improvement in self-gratification habits and improved attention in the child. Self-gratification behavior is a normal behavior in infants or children and is usually misdiagnosed. Treatment mainly constitutes neurodevelopment, sensory integration techniques, and parent education.